ANALISIS PREFERENSI KONSUMEN TERHADAP PEMILIHAN LEMBAGA PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) DI SURABAYA - Suryadi Kusniawan; Thomas Stefanus Kaihatu (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the preferences of foreign speakers in selecting institutions for learning Bahasa Indonesia for Foreign Speakers (BIPA) in Surabaya. Using a conjoint analysis approach, the study identifies the most influential service attributes and attribute combinations in consumer decision-making. Four main attributes were examined: learning model, class size, schedule flexibility, and learning facilities. Data were collected from 34 foreign respondents using a profile-based questionnaire. The findings indicate that learning schedule and learning facilities are the primary attributes considered by foreign nationals in choosing a BIPA institution in Surabaya. The most preferred BIPA institution profile among foreign consumers is one that offers a blended learning model, small or large class sizes, weekend learning schedules, and comprehensive learning facilities. These findings provide strategic input for BIPA providers in designing services aligned with foreign learners' preferences. Keywords: Consumer Preference, BIPA, Conjoint Analysis, Surabaya, Language Education